Powder-Mixed Micro-Electro-Discharge Machining-Induced Surface Modification of Titanium Alloy for Antibacterial Properties - Nurlan Nauryz; Salikh Omarov; Ainur Kenessova; Tri T. Pham; Didier Talamona; Asma Perveen (Journal of Manufacturing and Materials Processing, 2023)
The powder-mixed electro-discharge machining (PM-EDM) technique has shown its advantages in forming surfaces and depositing elements on the machined surface. Moreover, using hydroxyapatite (HA) powder in PM-EDM enhances the biocompatibility of the implant’s surfaces. Ti-6Al-4V alloy has tremendous advantages in biocompatibility over other metallic biomaterials in bone replacement surgeries. However, the increasing demand for orthopedical implants is leading to a more significant number of implant surgeries, increasing the number of patients with failed implants. A significant portion of implant failures are due to bacterial inflammation. Despite that, there is a lack of current research investigating the antibacterial properties of Ti-6Al-4V alloys. This paper focuses on studying the performance of HA PMEDM on Ti-6Al-4V alloy and its effects on antibacterial properties. By changing the capacitance (1 nF, 10 nF and 100 nF), gap voltage (90 V, 100 V and 110 V) and HA powder concentration (0 g/L, 5 g/L and 10 g/L), machining performance metrics such as material removal rate (MRR), overcut, crater size and hardness were examined through the HA PM micro-EDM (PM-μ-EDM) technique. Furthermore, the surface roughness, contact angle, and antibacterial properties of HA PM micro-wire EDM (PM-μ-WEDM)-treated surfaces were evaluated. The antibacterial tests were conducted for Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli, and Bacillus subtilis bacteria. The key results showed a correlation between the discharge energy and powder concentration with the antibacterial properties of the modified surfaces. The modified surfaces exhibited reduced biofilm formation under low discharge energy and a 0 g/L powder concentration, resulting in a 0.273 μm roughness. This pattern persisted with high discharge energy and a 10 g/L powder concentration, where the roughness measured 1.832 μm. Therefore, it is possible to optimize the antibacterial properties of the surface through its roughness.